2021
DOI: 10.1177/00031348211047487
|View full text |Cite
|
Sign up to set email alerts
|

High Failure Rate Following Restorative Surgery for Rectal Prolapse in Systemic Sclerosis Patients

Abstract: Introduction Systemic sclerosis (SSc) is a rare autoimmune connective tissue disorder. Colonic disorders are reported in 70% of patients. Only a few cases of rectal prolapse surgical repair in SSc patients were published, demonstrating high recurrence rate following any restorative surgery. The aim of this study is to present our surgical experience combined with the reported cases of SSc patients who underwent surgical interventions for rectal prolapse. Methods We reviewed our data and the published reports i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this scenario, patients will perceive a bulging sensation in their anus and complain of chronic stool leakage [76]. One small study reported a high recurrence rate of rectal prolapse occurs after restorative surgery [77], rendering the treatment of this complication challenging. Other anorectal clinical manifestations include haemorrhoids, which can develop secondary to chronic constipation in SSc.…”
Section: Upper Gastrointestinal Tract Involvementmentioning
confidence: 99%
“…In this scenario, patients will perceive a bulging sensation in their anus and complain of chronic stool leakage [76]. One small study reported a high recurrence rate of rectal prolapse occurs after restorative surgery [77], rendering the treatment of this complication challenging. Other anorectal clinical manifestations include haemorrhoids, which can develop secondary to chronic constipation in SSc.…”
Section: Upper Gastrointestinal Tract Involvementmentioning
confidence: 99%